New Directions of Mediation Development in Ukraine - K. S. Tokarieva (Bulletin of Kharkiv National University of Internal Affairs)
The rapid development of public relations in view of the spread of the new disease and acute crisis has an impact on all social institutions without exception. Mediation is no exception, so the current subject of the research is the analysis of new areas of the development of the social and legal institution of mediation in Ukraine. The purpose of the article is to identify new areas of mediation development in Ukraine, taking into account the impact of the COVID-19 pandemic on the most important areas of public life. In accordance with the purpose, the following tasks are formulated: to research the features of mediation in the field of health care; to study the development of online mediation; to study the features of school mediation as a mean of combating bullying. The research was based on a forecasting method to determine the perspectives for the use of mediation to resolve acute social conflicts.